Analysis of the Usefulness of Measurement on a Board at Ground Level for Assessing the Noise Level from a Wind Turbine - WSZOŁEK, Tadeusz; PAWLIK, Paweł; MLECZKO, Dominik; CHRONOWSKA, Jagna (Archives of Acoustics, 2020)
The specific working conditions of the wind turbine in strong wind cause a number of problems in the measurement of noise indicators used in its short and long-term assessment. The wind is a natural working environment of the turbine, but it also affects the measurement system, moreover, it can be a secondary source of other sounds that interfere with the measurement. One of the effective methods of eliminating the direct impact of wind on the measurement system is placing the microphone on the measurement board at ground level. However, the obtained result can not be directly compared with the admissible values, as it has to be converted to a result at a height of 4 m. The results of previous studies show that this relation depends, inter alia, on the speed and direction of the wind. The paper contains the results of measurements on the measurement board, according to EN 61400-11:2013, and at a height of 4 m above ground made simultaneously in three points around the 2 MW turbine at various instantaneous speeds and changing wind directions. Analysis of the impact of measuring point location on the measurement result of noise indicators and the occurrence of additional features affecting the relationship between the values measured on the board and at the height of 4 m, and especially the tonality, amplitude modulation and content of low frequency content, was made.